Mentalizing Adolescence: Reflective Functioning Capacities in Parents of Identical Twins and its Relationship to Adolescent Attachment - Tohme, Pia (2014)
Previous behavioural genetics studies have converged in finding a shared influence of maternal sensitivity on attachment security at age 1 but contradictory findings were reached when investigating its non-shared effect on attachment organization. However, to date, no research has investigated this association in adolescence. This study was the first aiming to investigate reflective functioning capacities in both, mothers and fathers of adolescent identical twins, and understanding the nature of its relationship to adolescent attachment coherence. One hundred families were interviewed, with each parent asked to complete the Parent Development Interview twice, once about each twin. Adolescent attachment was assessed using a semi-structured interview, the Child Attachment Interview. This study provided some support for predictions of attachment theory suggesting a shared environmental effect of parental reflective on the shared variance in adolescent attachment coherence. Thus, the similarity between twins’ coherence scores was partially explained by consistencies in their experience of parental reflective functioning. Examining maternal and paternal RF separately, strong associations were found between mothers’ and fathers’ RF scores, which were found to, partially independently, influence twins’ coherence scores at a family level only. This study did not quantitatively identify non-shared environmental influences of parental RF which, it was suggested, could reflect some shared genetic effects from twins to parent. Finally, based on a case study analysis, it was suggested that the interaction between a number of non-shared factors, such as twins’ level of psychological maturity, their potential de-identification from each other and from their parents, their perception of the twinship relationship and the parents’ description of each twin, could explain discrepancies between twins’ attachment classification.